Inovação em órgãos públicos de controle: a implantação do centro de pesquisa e inovação do Tribunal de Contas da União - Souza, Daniel Façanha Rocha de (2018)
The creation of the Centro de Pesquisa e Inovação (CePI) at Tribunal de Contas da União took place in 2015 with the aim of promoting and supporting the conception, development and application of new ideas and techniques to the activities of a government oversight body (BRASIL, 2015b). In order to analyze innovation in the public sector, Isidro-Filho (2017) established an applicable model in the federal public administration to describe the innovative process composed of antecedents of innovation; activities related to the innovation cycle; capabilities or resources for innovation; and results or impacts of innovation. Thus, the purpose of this study is to analyze the process of creating an innovation laboratory to assist in the innovative process in a public control body. Therefore, a study case was carried out through field and documentary research at the Tribunal de Contas da União, and also a qualitative study having as unit of analysis the Tribunal de Contas da União, using as main instrument of data collection the application of a questionnaire built based on the framework developed by Isidro- Filho (2017) applicable to Brazilian federal public administration. The results of the analyzes show that the main antecedent of the creation of CePI was the political impulse. The main barrier and the main facilitator were, respectively, the overlap of competencies and the choice of the members of CePI. With regard to co-creation, NESTA played a fundamental role in the conception of CePI in training and coaching in order to assimilate the methodology developed by that institution. In terms of innovation capacity, mainly transformative leadership and the strategic intention to innovate were identified. With respect to the innovation process to create CePI, the ideation was mainly supported of benchmarking with private companies and other innovation laboratories, in particular NESTA, with its diffusion in different ways (intranet and success of the works carried out). In addition, co-creation during the innovation process was verified through interorganizational learning among public organizations. The results obtained by TCU with the creation of CePI can be seen in the improvement of work processes; in greater efficiency and effectiveness by indirectly leveraging its objectives; increase their visibility; in the realization of new partnerships as a result of the creation of CePI; and improvement in working conditions.